2012
DOI: 10.2174/1874364101206010019
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Cutting of Posterior Lamellar Corneal Grafts by a Femtosecond Laser

Abstract: Purpose Posterior lamellar grafting of the cornea has become the preferred technique for treatment of corneal endothelial dysfunction. Posterior lamellar grafts are usually cut by a micro-keratome or a femto-second laser after the epithelial side of the donor cornea has been applanated. This approach often results in variable central graft thickness in different grafts and an increase in graft thickness towards the periphery in every graft. The purpose of this study was to evaluate if posterior lamellar grafts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 5 publications
2
26
0
2
Order By: Relevance
“…Visually compromising interface haze seems to be a significant limitation for the use of femtosecond lasers in posterior lamellar donor preparation. 11,16 Two patients were regrafted after 1 and 3 years because of progressive fibrous contraction of the lamellar graft. It is speculated that an asymmetric peripheral thickness of the DSAEK graft may induce this type of progressive contraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Visually compromising interface haze seems to be a significant limitation for the use of femtosecond lasers in posterior lamellar donor preparation. 11,16 Two patients were regrafted after 1 and 3 years because of progressive fibrous contraction of the lamellar graft. It is speculated that an asymmetric peripheral thickness of the DSAEK graft may induce this type of progressive contraction.…”
Section: Discussionmentioning
confidence: 99%
“…In one case, a VisuMax femtosecond laser (Carl Zeiss Meditec, Jena, Germany) was used to prepare the graft; for details, see Hjortdal et al 11 Posterior lamellar grafts were punched out to a diameter of 8.00 mm and either taco-folded and inserted with a forceps (first 17 eyes) or pulled into the anterior chamber using a Busin glide and forceps (last 85 eyes). At the end of surgery, the anterior chamber was filled with a large air bubble while the patient was left in a supine position.…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…This result has important implications as it suggests that the LDV FS laser may produce a smoother graft-host interface, which has been associated with better visual outcomes. 17,19 With the LDV FS laser the attempted dissection depth was closer to achieved depth and more predictable than with the ONE Microkeratome. These results correspond with the results of Price et al who found that ONE Microkeratome with the 350 µm head the achieved dissection depth approximately 100 µm greater than intended.…”
Section: Discussionmentioning
confidence: 87%
“…Neff and colleagues (10) reported that grafts ≤131 µm provided a statistically significant improvement in best-corrected visual acuity compared with thicker grafts. Several attempts have been made to develop a technique to create very thin DSAEK grafts, without wasting donor tissue (18)(19)(20)(21). A FS laser, without a microkeratome, was previously used for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…However, the resulting surface was not as smooth as from a microkeratome and concentric folds would form due to compression or irregularity of the posterior stroma (22,23). In addition, interface scatter may later appear (21). The method we describe here, the double-pass technique, combines the sequential use of a FS laser and a microkeratome.…”
Section: Discussionmentioning
confidence: 99%